Antimicrobial activity of in-situ bacterial nanocellulose-zinc oxide composites for food packaging - Silva, Francisco A. G. Soares (2023)
Active substances such as zinc oxide nanoparticles (ZnO) have been extensively explored due to their antimicrobial properties, low cost and scalability. Yet, their effectiveness is highly dependent on their morphology and specific surface area. Bacterial nanocellulose (BNC) is a suitable carrier due to its ability to transport and deliver active substances. In the case of nanocellulose-ZnO composites, conclusions drawn from antimicrobial studies are often based on only a few representatives of Gram-positive and Gram-negative bacteria. A more comprehensive study using different species and strains, and different methods to assess antimicrobial activity is required. Therefore, in this work, the antimicrobial activity of ZnO suspensions and BNCZnO films was assessed against a wide range of Gram-negative and Gram-positive bacteria using disc diffusion and viable cell count assays. Regarding the results of the disc diffusion assay, the increase of ZnO content (21–27% mZn/mBNCZnO) (in both ZnO suspensions and BNCZnO films), increased antimicrobial activity against all Gram-negative bacteria tested and some Gram-positive bacteria. In the viable cell count assay, BNCZnO films were effective against Escherichia coli (3 log reduction) and Listeria monocytogenes (1–3 log reduction) after 24 h. Low temperatures reduced the antimicrobial activity of BNCZnO.